2019
DOI: 10.3390/ijerph16071232
|View full text |Cite
|
Sign up to set email alerts
|

WHO Thematic Platform for Health Emergency and Disaster Risk Management Research Network (TPRN): Report of the Kobe Expert Meeting

Abstract: The WHO Thematic Platform for Health Emergency and Disaster Risk Management Research Network (TPRN) was established in 2016 in response to the Sendai Framework for Disaster Risk Reduction 2015–2030. The TPRN facilitates global collaborative action for improving the scientific evidence base in health emergency and disaster risk management (Health EDRM). In 2018, the WHO convened a meeting to identify key research questions, bringing together leading experts from WHO, TPRN, World Association for Disaster and Eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 3 publications
0
34
0
Order By: Relevance
“…The Asia Pacific Disaster Mental Health Network was established to foster advancements and coordination of psychosocial supports and mental health service delivery, policy development and collaborative research in the region. In line with the priorities of the WHO Thematic Platform for Health EDRM and its research network [ 12 , 72 ], the Asia Pacific Network aims to contribute to improvements in mental healthcare and psychosocial support through rigorous research and policy. Within the context of the COVID-19 pandemic and recent climatic hazards, the network set an agenda that prioritises strengthened community engagement, improved capacity for mental health and community services to respond to the needs of disaster-affected populations, integrating emerging technologies, addressing the impacts of climate change and supporting high-risk groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Asia Pacific Disaster Mental Health Network was established to foster advancements and coordination of psychosocial supports and mental health service delivery, policy development and collaborative research in the region. In line with the priorities of the WHO Thematic Platform for Health EDRM and its research network [ 12 , 72 ], the Asia Pacific Network aims to contribute to improvements in mental healthcare and psychosocial support through rigorous research and policy. Within the context of the COVID-19 pandemic and recent climatic hazards, the network set an agenda that prioritises strengthened community engagement, improved capacity for mental health and community services to respond to the needs of disaster-affected populations, integrating emerging technologies, addressing the impacts of climate change and supporting high-risk groups.…”
Section: Resultsmentioning
confidence: 99%
“…In response, the Asia Pacific Disaster Mental Health Network was established in June 2020 to create a collaborative platform for rigorous research, evidence-based practice and tailored policy designed to support improvements in mental health among disaster-affected communities. The network is supported by the World Health Organization (WHO) Thematic Platform for Health Emergency and Disaster Risk Management (Health EDRM) and its research network [ 12 ]. At its formation, the network represented seven Asian-Pacific nations, and it is growing.…”
Section: Introductionmentioning
confidence: 99%
“…We share the recommendation expressed in the WHO Health-EDRM framework [ 1 ] regarding future research needs: a holistic all-hazard perspective across all disaster-management phases which includes physical, mental, and psychosocial needs. In order to achieve this, multidisciplinary and multi-sectoral collaboration between science, policy makers and practitioners is needed [ 39 , 44 , 45 ]. Such an exchange and dialogue between stakeholders is important in order to identify knowledge gaps, jointly develop knowledge, and, finally, to put scientific findings into practice [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…This framework also provides a useful paradigm within which to shape the research field's strategic development. The WHO's Thematic Platform for Health-EDRM [19] was established, and five primary research areas on DRR were identified by an international research network [20].…”
Section: Introductionmentioning
confidence: 99%